Etiological and epidemiological characteristics of surgically treated radial nerve lesions: A 20-year single-center experience - Rasulić, Lukas; Đjurašković, Slavko; Lakićević, Novak; Lepić, Milan; Savić, Andrija; Grujić, Jovan; Mićić, Aleksa; Radojević, Stefan; Córdoba-Mosqueda, María Elena; Visani, Jacopo; Puzović, Vladimir; Kovačević, Vojin; et al. (Frontiers in Surgery, 2022)
Introduction: Radial nerve lesions present a clinical entity that may lead to disability, psychological distress, and a job loss, thus requires great attention. Knowledge of etiology and exact mechanism of the nerve impairment is of great importance for appropriate management of these patients, and there are only a few papers focused on these features in patients with surgically treated radial nerve lesions. The lack of studies presenting the etiology and injury mechanisms of surgically treated radial nerve lesions, may be due to a relatively small number of specialized referral centers, and dispersion to low-flow centers, as well as a greater focus on the surgical treatment outcomes. Aim: The aim of this study was to describe etiological and epidemiological characteristics of patients with surgically treated radial nerve lesions of various origin. Methods: This retrospective study evaluated 147 consecutive patients with radial nerve lesion, treated in the Department during the last 20 years, from January 1st, 2001 until December 31st, 2020 with a follow-up of at least one year. Results: The vast majority of patients belonged to the working population, and 70.1% of them were male. Most commonly, the etiology of nerve lesion was trauma (63.3%) or iatrogenic injury (28.6%), while the less common origin was idiopathic (4.1%) or neoplastic (4.1%). The most frequent location of the lesion was in the upper arm, followed by the elbow, and forearm. Fracture related contusion was the most common mechanism (29.9%), followed by postoperative fibrosis (18.4%), lacerations (18.4%), and compression (15.6%). Conclusion: Based on the fact that traumatic or iatrogenic injuries constitute the majority of cases, with their relevant mechanisms, and upper arm predomination, it is crucial to raise awareness and understanding of the radial nerve injuries among orthopaedic surgeons to decrease the numbers of these patients, and properly preserve or treat them within the initial surgery.